Adjuvant radiotherapy for patients with clinical T3–4 oral and oropharyngeal cancer who achieved major pathologic response after neoadjuvant immunochemotherapy and surgery: a propensity score-matched retrospective study - Li, Menghua; Yang, Shiyan; Liu, Lili; Hu, Wanming; Yan, Shida; Zhang, Yani; Du, Mingyuan; Gao, Xianlu; Yang, Chulin; Zheng, Liji; Chen, Chunyan; Zhou, Jian; et al. (Frontiers in Immunology, 2026)
BackgroundNeoadjuvant chemotherapy combined with immunotherapy results in high pathologic response rates in locally advanced oral and oropharyngeal cancer (OC/OPC). It is unclear if patients with clinical T3-4 (cT3-4) OC/OPC at initial diagnosis can safely omit adjuvant radiotherapy (ART) after significant pathological downstaging.MethodsThis retrospective cohort study included cT3–4 OC/OPC patients who achieved a major pathologic response (MPR) after neoadjuvant immunochemotherapy between July 2019 and May 2024. Patients were categorized by whether they received ART. Propensity score matching was used to balance baseline characteristics. Local recurrence-free survival (LRFS), locoregional recurrence-free survival (LRRFS), distant metastasis-free survival (DMFS), and overall survival (OS) were compared between cohorts.ResultsA total of 247 patients were eligible, with a median follow-up of 31 months (IQR, 20-41). The 2-year survival outcomes were favorable: LRFS 93.4%, LRRFS 85.0%, DMFS 95.6%, and OS 93.0%. In the matched cohorts (74 pairs), ART significantly improved 2-year LRFS (100% vs. 85.5%, p = 0.001), and LRRFS (91.5% vs. 77.5%, p = 0.014), but not DMFS (96.4% vs. 95.6%, p = 0.740), and OS (96.5% vs. 90.0%, p = 0.093). These benefits remained significant among patients with ypT0–2 tumors after matching.ConclusionsOmitting ART in patients with cT3–4 OC/OPC who achieve MPR after neoadjuvant immunochemotherapy and surgery significantly compromises oncological outcomes. Further investigation is necessary to optimize adaptive de-escalation strategies for this population.